2019
DOI: 10.3390/s19092095
|View full text |Cite
|
Sign up to set email alerts
|

On Placement, Location and Orientation of Wrist-Worn Tri-Axial Accelerometers during Free-Living Measurements

Abstract: Wearable accelerometers have recently become a standalone tool for the objective assessment of physical activity (PA). In free-living studies, accelerometers are placed by protocol on a pre-defined body location (e.g., non-dominant wrist). However, the protocol is not always followed, e.g., the sensor can be moved between wrists or reattached in a different orientation. Such protocol violations often result in PA miscalculation. We propose an approach, PLOE (“Placement, Location and Orientation Evaluation meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Accelerometry is considered the standard for objectively measuring SB, and has been shown to provide valid estimates of SB. Wrist-worn Actigraph accelerometers have been widely used for measuring PA, and have been shown to increase wear compliance in participants in free-living conditions [ 76 , 77 , 78 , 79 , 80 ]. In terms of sleep, we realize that polysomnography is considered the golden standard for measuring sleep objectively, providing detailed information about different sleep stages and sleep patterns [ 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accelerometry is considered the standard for objectively measuring SB, and has been shown to provide valid estimates of SB. Wrist-worn Actigraph accelerometers have been widely used for measuring PA, and have been shown to increase wear compliance in participants in free-living conditions [ 76 , 77 , 78 , 79 , 80 ]. In terms of sleep, we realize that polysomnography is considered the golden standard for measuring sleep objectively, providing detailed information about different sleep stages and sleep patterns [ 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, it is reported in one study [ 73 ] that the participants tend to prefer this configuration since sensors are more comfortable and less cumbersome to wear on the wrist. However, it is important to notice that another study [ 91 ] has shown that 15.6% of their participants who wore accelerometers on the wrist violated the protocol for one or more days. Sensors were worn on the wrong hand during 6.9% of the days and during the periods of discrepancies, the daily PA was miscalculated by more than 20%.…”
Section: Sensorsmentioning
confidence: 99%
“…The last case observed mostly in FLEs situations is “complete freedom”. Participants are thus equipped with one or more IMUs and continue their daily and usual activities at home (including going to work, hobbies, and home activities) without any instruction or suggestion [ 6 , 7 , 17 , 27 , 38 , 39 , 44 , 60 , 69 , 72 , 73 , 74 , 75 , 80 , 89 , 91 , 100 , 104 , 104 ]. In the latter case, the participant is in the most natural conditions possible (both environment and activity).…”
Section: Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Present-day micromechanical accelerometers are widely used in different types of transport and electronic means from aerospace, water and auto transport systems to mobile phones and new generation video game consoles [1][2][3][4][5][6]. There are many kinds of transducers in present micromechanical accelerometers, such as capacitive, piezo-resistive, electromagnetic, optical, thermal convective, acoustic waves resonant, field emission, tunnel transducers and so on [6].…”
Section: Introductionmentioning
confidence: 99%